Characterization and target genes of nine human PRD-like homeobox domain genes expressed exclusively in early embryos - Madissoon, Elo (Sci Rep, 2016)
PAIRED (PRD)-like homeobox genes belong to a class of predicted transcription factor genes. Several of these PRD-like homeobox genes have been predicted in silico from genomic sequence but until recently had no evidence of transcript expression. We found recently that nine PRD-like homeobox genes, ARGFX, CPHX1, CPHX2, DPRX, DUXA, DUXB, NOBOX, TPRX1 and TPRX2, were expressed in human preimplantation embryos. In the current study we characterized these PRD-like homeobox genes in depth and studied their functions as transcription factors. We cloned multiple transcript variants from human embryos and showed that the expression of these genes is specific to embryos and pluripotent stem cells. Overexpression of the genes in human embryonic stem cells confirmed their roles as transcription factors as either activators (CPHX1, CPHX2, ARGFX) or repressors (DPRX, DUXA, TPRX2) with distinct targets that could be explained by the amino acid sequence in homeodomain. Some PRD-like homeodomain transcription factors had high concordance of target genes and showed enrichment for both developmentally important gene sets and a 36 bp DNA recognition motif implicated in Embryo Genome Activation (EGA). Our data implicate a role for these previously uncharacterized PRD-like homeodomain proteins in the regulation of human embryo genome activation and preimplantation embryo development.